Formulation and Physical Quality Test of Chinese Petai Leaf Gel Extract (leucaena leucocephala) - Sugiyarto, Sugiyarto (Universitas Aisyah Pringsewu, 2024)
Petai Cina leaves (leucaena leucocephala) contain flavonoids, saponins and tannins. Based on previous research, it has been proven that this group of compounds has activity as a burn wound healer. Therefore, it is necessary to develop a dosage form from petai cina leaves as a medicine for burns in the form of a gel dosage form. The aim of this research was to determine the physical quality of petai cina leaf extract. In this study, the extract was obtained using the maceration method with 70% ethanol solvent. Next, the extract was made into a gel preparation using a hydrophilic base with an extract concentration of 15% and 30%. The gel preparation was then evaluated for physical properties including organoleptic test, homogeneity test, pH test, adhesion test. The test results show that the physical test results obtained are in accordance with the requirements for the physical properties of the gel preparation